2020
DOI: 10.20944/preprints202012.0632.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antimicrobial Use, Residues, Resistance and Governance in the Food and Agriculture Sectors, Tanzania

Abstract: All infections are potentially curable as long as the etiological agents are susceptible to antimicrobials. The increased rate at which antimicrobials are becoming ineffective is a global health risk of increasing concern that threatens withdrawal of beneficial antimicrobials for disease control. Increased demand for food of animal origin, in particular eggs, meat and milk has led to intensification and commercial production systems where excessive use and misuse of antimicrobials may prevail. Antimicrobials, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…For instance, Escherichia coli strains resistant to amoxicillin + clavulanate, sulphamethoxazole and neomycin, Methicillin Resistant Staphlococcus aureus (MRSA) and Extended-Spectrum Beta-Lactamase (ESBL) is also found in the livestock sector. 8 Similarly, in Nepal, a study observed the presence of 103 gram-negative bacteria isolated from 38 meat samples. 21 Citrobacter species, Salmonella species, Proteus species, E. coli, Pseudomonas species andKlebsiella species were seen, where E. coli showed resistance of Ampicillin followed by Colistin and Polymyxin B.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For instance, Escherichia coli strains resistant to amoxicillin + clavulanate, sulphamethoxazole and neomycin, Methicillin Resistant Staphlococcus aureus (MRSA) and Extended-Spectrum Beta-Lactamase (ESBL) is also found in the livestock sector. 8 Similarly, in Nepal, a study observed the presence of 103 gram-negative bacteria isolated from 38 meat samples. 21 Citrobacter species, Salmonella species, Proteus species, E. coli, Pseudomonas species andKlebsiella species were seen, where E. coli showed resistance of Ampicillin followed by Colistin and Polymyxin B.…”
Section: Introductionmentioning
confidence: 97%
“…For instance, a study has shown the use of oxytetracycline (OTC) to prevent transit fever caused by Pasteurella multocida, in animals during their transportation. 8 A study in Morogoro, 90% of broiler farmers frequently used tetracycline, amprolium, sulphonamides, trimethoprim, neomycin and flumequine in their chicken flocks. 9,10 Similarly, another study has reported the presence of antimicrobials reissued in 76.4% of broiler meat samples.…”
Section: Introductionmentioning
confidence: 99%
“…Farmers may only give antibiotics under the supervision of a veterinarian. Hence, they may not provide antibiotics as feed additives or prevent disease, administer vaccines, promote sound farming practices, and apply biosecurity without professional guidance [6,10,11]. Control efforts will be challenging to implement without various data related to antibiotic use.…”
Section: Introductionmentioning
confidence: 99%
“…Mdegela et al. indicated that the Tanzanian NAP has led to improved coordination of the committee for implementation of activities, better community awareness, development of surveillance sites and successful guideline establishment ( Mdegela et al. , 2021 ).…”
Section: Introductionmentioning
confidence: 99%